2016
DOI: 10.1007/s12265-015-9668-7
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Nerve Stimulation Evoked Heart Rate Changes and Protection from Cardiac Remodeling

Abstract: This study investigated whether vagal nerve stimulation (VNS) leads to improvements in ischemic heart failure via heart rate modulation. At 7 ± 1 days post left anterior descending artery (LAD) ligation, 63 rats with myocardial infarctions (MI) were implanted with ECG transmitters and VNS devices (MI + VNS, N = 44) or just ECG transmitters (MI, N = 17). VNS stimulation was active from 14 ± 1 days to 8 ± 1 weeks post MI. The average left ventricular (LV) end diastolic volumes at 8 ± 1 weeks were MI = 672.40 μl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The intermittent stimulation of the DVMN (which lacks major chronotropic effects) preserved cardiac function in rats with MI (as shown in this study), which was consistent with the results of some previous reports that suggested that the beneficial effects of VNS in heart failure were not entirely dependent on lowering heart rate ( 13 , 14 , 15 ). This was an important conclusion to draw in the context of a strong clinical association between low chronotropic vagal tone and the risk of death after MI or in established heart failure ( 40 , 41 ), and of the effectiveness of pharmacological interventions that lower heart rate (e.g., β-blockers and I f inhibitors) ( 42 , 43 , 44 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The intermittent stimulation of the DVMN (which lacks major chronotropic effects) preserved cardiac function in rats with MI (as shown in this study), which was consistent with the results of some previous reports that suggested that the beneficial effects of VNS in heart failure were not entirely dependent on lowering heart rate ( 13 , 14 , 15 ). This was an important conclusion to draw in the context of a strong clinical association between low chronotropic vagal tone and the risk of death after MI or in established heart failure ( 40 , 41 ), and of the effectiveness of pharmacological interventions that lower heart rate (e.g., β-blockers and I f inhibitors) ( 42 , 43 , 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…Selective efferent VNS applied in this study was likely to activate some or all of these mechanisms, whereas the observed effects of optogenetic stimulation of the DVMN on myocardial function in sham-operated animals suggested a plausible additional and/or alternative mechanism. Surprisingly, the effect of long-term VNS on a healthy heart has never been described, because the design of all of the preceding studies that investigated the effect of VNS in heart failure ( 12 , 13 , 14 , 15 , 17 ) excluded the experimental group(s) of healthy subjects (“sham heart failure” groups) receiving the stimulation. In this study, we observed proportionally similar improvements in key measures of LV systolic function and exercise capacity in groups of rats with permanent LAD occlusion and in sham-operated animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic nervous system dysfunction, due to excessive sympatho-excitation and withdrawal of parasympathetic (vagal) tone, is a key mechanism of heart failure ( Binkley et al, 1991 ; Floras and Ponikowski, 2015 ). VNS increased survival, slowed down the progression of myocardial remodeling, and improved ventricular function in numerous experimental models of heart failure ( Li et al, 2004 ; Agarwal et al, 2016 ) as well as in some clinical studies ( De Ferrari et al, 2010 ; Premchand et al, 2014 ). Moderate electrical stimulation (up to 2 mA) applied to the cervical VN preferentially activates afferent sensory fibers, which have a lower activation threshold than efferent fibers.…”
Section: Applications Of Vnsmentioning
confidence: 99%
“…69 Xth nerve stimulation to increase parasympathetic tone and restore autonomic nervous system balance has been shown to slow the progression of myocardial remodeling and atrial and ventricular dysfunction in animal models of chronic heart failure. [70][71][72][73] However, cervical Xth nerve stimulation to increase parasympathetic activity as a treatment for heart failure has proved difficult to achieve. 74 The Xth nerve is a mixed nerve containing parasympathetic sensory (afferent), parasympathetic motor (efferent) fibers, and some sympathetic fibers; and nonselective stimulation of the cervical Xth nerve can generate highly varied responses because of recruitment of afferent, efferent, or both vagal fiber types.…”
Section: Myocardial Infarctionmentioning
confidence: 99%